Pengukuran perilaku dan niat beli produk kosmetik halal melalui modifikasi theory of planned behavior (TPB) - Kadengkang, Justi Aresta; Linarti, Utaminingsih (University of Muhammadiyah Malang, 2020)
Objectives: the purpose of this study was to study the relationship attitudes, subjective norms and perceptual controls related to religiosity, and product knowledge about the purpose of buying and helping Muslim consumers in buying halal cosmetic products.Method: the subject in this study was Muslim students aged 17-23 years who were studying at State Universities (PTN) in the Province of Daerah Istimewa Yogyakarta. The sampling technique uses purposive sampling. The analytical method used is multiple linear regression. Data collection uses a closed questionnaire with a total of 275 respondents.Findings: the findings of this study indicate that religiosity, product knowledge, attitudes, subjective norms, and perception control have a positive and significant influence on consumers' intentions in buying halal cosmetic productsConclusions: it is expected to always pay attention and know the halal label and the content on the cosmetic products to be used,Â so as to Â avoid products that are not halal or have content that is prohibited by religion.